Sperm Chromatin Structure Assay (SCSA®) for Fertility Assessment. Issue 8 (4th August 2022) - Evenson, Donald P.
Abstract: The Sperm Chromatin Structure Assay (SCSA ® ) is a federally registered protocol for simultaneous flow cytometric measures of sperm DNA integrity and chromatin structure. Fresh or frozen/thawed raw semen samples are diluted in buffer to a sperm concentration of ∼1–2×10 6 /ml and then treated with a pH 1.20 buffer for 30 s to open the DNA strands at sites of DNA strand breaks. The sperm are then stained with acridine orange (AO) that intercalates into double‐strand DNA and fluoresces green (515–530 BP filter) and stacks on single‐strand DNA that fluoresces red (630 LP filter) upon excitation from a 488 nm laser. The extent of single and double DNA strand breaks (DNA fragmentation index, %DFI) and level of excess nuclear histones (high DNA stainable sperm, %HDS) are simultaneously measured in individual sperm. From the time a fresh or frozen/thawed semen sample is received at the site of a flow cytometer (FCM) programmed for the SCSA protocol, data can be obtained within about 10 min on 5–10×10 3 sperm. The %DFI and %HDS can be determined by computer‐gated regions on the green versus red cytogram. Alternatively, a determination is made by transforming the green versus red cytogram to a total DNA stainability (red + green fluorescence) versus red/red + green fluorescence cytogram from which a frequency histogram is produced and the %DFI calculated from it. The clinical threshold for human natural or IUI fertilization is 25% DFI at which point the ART lab should consider moving to ICSI fertilization. The clinical threshold for HDS is also 25%; values above this level may result in early embryo death due to abnormal gene readout caused by the abnormal tertiary structure of chromatin. Numerous lifestyle and environmental factors cause sperm DNA fragmentation. Reactive oxygen species (ROS) play a significant role in DNA breakage. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Sperm Chromatin Structure Assay (SCSA®) Basic Protocol 2 : SCSA data analysis: Calculations of %DFI and %HDS of semen samples by one of two methods Support Protocol 1 : SCSA sample collection and shipping Support Protocol 2 : Flow cytometer set up Support Protocol 3 : Selection and use of reference samples